The High Burden and Predictors of Anemia Among Infants Aged 6 to 12 Months in Dar es Salaam, Tanzania. Issue 1 (March 2022) - Lweno, Omar; Hertzmark, Ellen; Darling, Anne Marie; Noor, Ramadhani; Bakari, Leguma; Sudfeld, Christopher; Manji, Karim; Fawzi, Wafaie
Background: Despite several interventions, the prevalence of anemia and related complications remains high among infants in Tanzania. Objective: We sought to determine the predictors of iron-deficiency anemia (IDA) among infants of HIV-negative women in Dar es Salaam, Tanzania. Methods: Cross-sectional analysis of 2826 mother–infant pairs who participated in a trial of vitamins and perinatal outcomes in Dar es Salaam, Tanzania. Hemoglobin and mean corpuscular volume were used to determine the prevalence of anemia among infants at 6 and 12 months. Multiple logistic regression was used to determine the maternal and infant risk factors for anemia during infancy. Results: We found high prevalence of anemia (90%) and IDA (44.2%) among infants. Higher maternal education (odds ratio [OR] = 0.52), maternal normal hemoglobin at enrollment (OR = 0.68) and during the early postpartum period reduced the odds of IDA at 6 months (OR = 0.56). The odds of IDA at 6 months were higher among males (OR = 1.65), wealth score below median (OR = 1.35), low birth weight (LBW; OR = 1.75), and small for gestational age (SGA) infants below the third centile (OR = 1.95) or third to less than fifth centile (OR = 2.29). Higher maternal education lowered the odds of IDA at 12 months (OR = 0.25). Wealth score below median (OR = 1.44), preterm delivery (OR = 1.94), SGA (less than third centile; OR = 2.40), and LBW (OR = 2.89) increased the odds of IDA during infancy in the study population. Dietary diversity was low for infants and women in the study sample. Conclusion: Interventions to reduce the risk of infant IDA should address women's education, improvement of wealth status, and optimal care for premature, SGA, and LBW infants.